Metacognitive Ability Effect on Leadership Development - Emmanuel Mango; Jeremiah Koshal; Caren Ouma (Integrated Journal of Business and Economics (IJBE), 2019)
Leadership is the single most important element for the success of an organization. This explains why leadership skill is one of the most sought after skills. The only challenge is that effective leaders are few. Leadership development is meant to eradicate the shortage of leaders but there is a widespread outcry about the effectiveness of the current leadership interventions. Despite the huge expenditure in developing leaders, the outcomes are not comparable to the resources invested. Beyond the traditional elements (content, context, program length and delivery) of leadership development, the boundaries of research and practices have to be extended to the neglected elements of learning like metacognitive ability, hence this study examines the effect metacognitive ability on leadership development. The study was conducted among MBA students within private universities in Kenya. The sample size was 314 students, with a response rate of 92 percent. The results reveal that metacognitive ability significantly predicts leadership developments. The results imply that the higher the levels of metacognitive ability that leadership development participants have, the better they are at acquiring leadership skills.